Advancing feminist positioning in the field of transitional justice - Ní Aoláin, Fionnuala (International journal of transitional justice, 2012)
This article contributes to an ongoing conversation among feminist scholars about what constitutes feminist positioning with regard to the central issues that define transitions from conflict or repression towards more liberal polities. The analysis suggests that the feminist presence in transitional justice is complex, multilayered and still in the process of full engagement. Concentrating on the genealogy of this presence, the article reflects on what are commonly invoked scholarly and policy reference points, showing how little gender analysis and women’s issues entered into the discursive fray in the public and political arenas where the terminology of accountability emerged. The challenge in assessing feminist positioning is that an uncritical and narrowly liberal conception of gender equality directs our gaze away from the cultural, material and geopolitical sites in which transitional justice practices have emerged. The article explores the connections between transitional justice and identification of harms done to women, the importance of acknowledging these harms and the need to centre discussions of agency and autonomy in feminist approaches to structural political change in deeply divided societies.